2023
DOI: 10.1007/s10832-023-00324-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Fermi energy as common parameter to describe charge compensation mechanisms: A path to Fermi level engineering of oxide electroceramics

Andreas Klein,
Karsten Albe,
Nicole Bein
et al.

Abstract: Chemical substitution, which can be iso- or heterovalent, is the primary strategy to tailor material properties. There are various ways how a material can react to substitution. Isovalent substitution changes the density of states while heterovalent substitution, i.e. doping, can induce electronic compensation, ionic compensation, valence changes of cations or anions, or result in the segregation or neutralization of the dopant. While all these can, in principle, occur simultaneously, it is often desirable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 183 publications
0
19
0
Order By: Relevance
“…This is particularly relevant when cations possess multiple stable electronic configurations, as is the case with transition metal cations like Fe 3+ /Fe 4+ 84,85,86 . This means that the self‐trapping of holes results in polaron formation 87 . Polaron or trapping states have been identified in many iron‐doped perovskites, for example, Fe‐doped BT, 88 LiNbO 3 , 89 and SrTiO 3 materials 88 .…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly relevant when cations possess multiple stable electronic configurations, as is the case with transition metal cations like Fe 3+ /Fe 4+ 84,85,86 . This means that the self‐trapping of holes results in polaron formation 87 . Polaron or trapping states have been identified in many iron‐doped perovskites, for example, Fe‐doped BT, 88 LiNbO 3 , 89 and SrTiO 3 materials 88 .…”
Section: Resultsmentioning
confidence: 99%
“…For LaTaON 2 and La 0.9 Y 0.1 TaON 2 , within experimental uncertainty, the nominal compositions were confirmed by the refinements. It is important to note that the refinements of the La 0.9 Y 0.1 TaO 2 N compound revealed that the real composition was La 0.9 Y 0.1 TaO 1.58 (7) N 1.42 (7) . For LaTaO 2 N, the situation remained somewhat unclear as the free refinements strongly pointed to the presence of a N-rich composition.…”
Section: Long-range Structural Analysis Of (Lay)ta(on)mentioning
confidence: 99%
“…Inorganics 2024, 12, 90 2 of 18 Consequently, a change in the Fermi level and defects in the crystal structure, such as oxygen vacancies, can come as an effect of the partial substitution of oxygen by nitrogen [7]. What results is a link between anionic doping-and hence the anionic ordering-and the electronic structure, which is highly important to understand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike metals, the Fermi level can be altered by several electronvolts in many semiconductors by relatively minor changes in the defect chemistry. [24][25][26] Fermi level shifts cause the measured binding energy of the core lines to shift by an equivalent energy.…”
Section: Correlation Analysismentioning
confidence: 99%